Implementasi Islamic Parenting dalam Membentuk Karakter Religius Anak Keluarga Petani di Desa Bronjong Lamongan - Ibaadurrohman; Muhammad Arfan Mu’ammar; Muhammad Fazlur Rahman Hadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
In the context of farming communities which tend to have limited resources, the application of Islamic parenting principles is expected to have a positive impact on the formation of children's religious character. The research method used in this research is a qualitative approach with data collection techniques through interviews, observation and questionnaires. Research subjects included parents and children from farming families in Bronjong Village. The informants consisted of three farming families chosen randomly. This research aims to find out how parents make efforts to build religious character in the children of farming families in Bronjong Village, Lamongan. The research results show that: firstly, the implementation of Islamic parenting in Bronjong Village involves several key strategies, including religious education at home, application of Islamic moral values in daily activities, and participation in community religious activities. Both children's religious character is formed through consistency in the application of Islamic values and a supportive social environment. Thirdly, Islamic parenting can be an effective strategy in shaping children's religious character, even in the context of limited resources.